Gene Therapy in the Developing Countries - Chidi, Emengaha Festus; Johnkennedy, Nnodim; Hope, Okorie; Henry, Amah; Ukamaka, Edward (International Journal of Medical and Health Sciences Research, 2015)
Gene therapy is treatment directed to curing genetic disease by introducing normal genes into the patients in order to overcome the effects of abnormal genes using technique of genetic engineering. The most radical approach involves applying this at the early stage in the embrayo, so that the new gene would be incorporated into the germ cells and hence will be inheritable. This approach is not considered to be safe either safe or ethical because the consequences may affect the descendants of the patients. Therefore, this review throws more light on gene therapy, its application and consequences in the developing countries.